1996
DOI: 10.1128/jcm.34.1.175-176.1996
|View full text |Cite
|
Sign up to set email alerts
|

Field inversion gel electrophoretic analysis of Legionella pneumophila strains associated with nosocomial legionellosis in children

Abstract: Two nosocomial cases of Legionnaires' disease occurred in children. Legionella pneumophila serogroup 1 was isolated from both patients and 30 of 39 plumbing system sites in the hospital. The patient and hospital environmental isolates yielded identical field inversion gel electrophoretic patterns which differed from patterns observed with epidemiologically unrelated strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Legionella typing was performed in 33 out of 47 articles (72.3 %), mainly by PFGE (Venezia et al , 1994; Marrie et al , 1995; Mermel et al , 1995; Chang et al , 1996; Green et al , 1996; Lück et al , 1998; Campins et al , 2000; Knirsch et al , 2000; Trübel et al , 2002; Levy et al , 2003; Torii et al , 2003; Ozerol et al , 2006; Gudiol et al , 2007; Brûlet et al , 2008; Palmore et al , 2009) and amplified fragment length polymorphism (Campins et al , 2000; Jonas et al , 2000; Perola et al , 2002a; Bencini et al , 2005; Johansson et al , 2006; Fendukly et al , 2007; Mencacci et al , 2011). Other DNA fragment-based methods such as randomly amplified polymorphic DNA (Hoebe et al , 1998; Trübel et al , 2002; Perola et al , 2002a), restriction enzyme analysis (Lück et al , 1994; Bangsborg et al , 1995; Jonas et al , 2000), arbitrarily primed PCR (Berthelot et al , 1998; Jonas et al , 2000) and RFLP (Darelid et al , 1994) were less frequently reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Legionella typing was performed in 33 out of 47 articles (72.3 %), mainly by PFGE (Venezia et al , 1994; Marrie et al , 1995; Mermel et al , 1995; Chang et al , 1996; Green et al , 1996; Lück et al , 1998; Campins et al , 2000; Knirsch et al , 2000; Trübel et al , 2002; Levy et al , 2003; Torii et al , 2003; Ozerol et al , 2006; Gudiol et al , 2007; Brûlet et al , 2008; Palmore et al , 2009) and amplified fragment length polymorphism (Campins et al , 2000; Jonas et al , 2000; Perola et al , 2002a; Bencini et al , 2005; Johansson et al , 2006; Fendukly et al , 2007; Mencacci et al , 2011). Other DNA fragment-based methods such as randomly amplified polymorphic DNA (Hoebe et al , 1998; Trübel et al , 2002; Perola et al , 2002a), restriction enzyme analysis (Lück et al , 1994; Bangsborg et al , 1995; Jonas et al , 2000), arbitrarily primed PCR (Berthelot et al , 1998; Jonas et al , 2000) and RFLP (Darelid et al , 1994) were less frequently reported.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, special attention should be devoted to children, who are rarely affected by waterborne infections of community origin. We found nine articles where hospitalized neonates, in some cases premature and/or receiving corticosteroids, got Legionella pneumonia directly from water or from mechanical ventilation (Aubert et al , 1990; Holmberg et al , 1993; Lück et al , 1994; Green et al , 1996; Campins et al , 2000; Franzin et al , 2001; Trübel et al , 2002; Johansson et al , 2006; Shachor-Meyouhas et al , 2010). Another 32 articles where neonates or children were affected by other waterborne bacteria are described (Pazzaglia et al , 1990; Lacey & Want, 1991; Wang et al , 1991; Pegues et al , 1994; Buttery et al , 1998; Ferroni et al , 1998; Muyldermans et al , 1998; Verweij et al , 1998; Kappstein et al , 2000; Maroye et al , 2000; Hoque et al , 2001; Jeong et al , 2001; Su et al , 2001; Vochem et al , 2001; Perola et al , 2002b; Mittal et al , 2003; Kendirli et al , 2004; Kline et al , 2004; Moreira et al , 2005; Aumeran et al , 2007; Kilic et al , 2007; Lee, 2008; Kotsanas et al , 2008; Livni et al , 2008; Randrianirina et al , 2009; Naze et al , 2010; Lucero et al , 2011; Mosayebi et al , 2011; Mutlu et al , 2011; Hong et al , 2012; Schneider et al , 2012; Yapicioglu et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nasogastric tubes have been implicated in legionnaires' disease, presumably by microaspiration of contaminated water. 9 A pseudoepidemic has been reported in which contaminated bronchoscopes resulted in falsepositive cultures from clinical samples taken at bronchoscopy from healthy patients. 10 This report does not represent a pseudoepidemic because clinical infection was present and Legionella was confirmed to be the etiologic agent by Legionella antibody seroconversion or a positive result on the urinary antigen test in each patient.…”
Section: Discussionmentioning
confidence: 99%